ASP 3 fast & easy web development - Thomasson, Michael D. (Prima Tech, 2000)
You don't have to spend your time wading through manuals to learn Active Server Pages. Spend it doing what you do best—creating Web pages! Get your foot in the door with ASP by learning about ASP objects, VBScript, ADO, SQL, and COM/COM+. Build high performance, scalable Web applications in no time! The Premier Press Fast & Easy TM Web Development series combines easy-to-understand instructions with visual examples. The result is a unique, hands-on approach to ASP that you won't find anywhere else. Less time, less effort, more results!